Degeneration of serotonin neurons triggers spasticity in amyotrophic lateral sclerosis. Issue 3 (22nd September 2017) - El Oussini, Hajer; Scekic‐Zahirovic, Jelena; Vercruysse, Pauline; Marques, Christine; Dirrig‐Grosch, Sylvie; Dieterlé, Stéphane; Picchiarelli, Gina; Sinniger, Jérôme; Rouaux, Caroline; Dupuis, Luc
Abstract : Objective: Spasticity occurs in a wide range of neurological diseases, including neurodegenerative diseases, after trauma, and after stroke, and is characterized by increased reflexes leading to muscle hypertonia. Spasticity is a painful symptom and can severely restrict everyday life, but might also participate in maintaining a low level of motor function in severely impaired patients. Constitutive activity of the serotonin receptors 5‐HT2B/C is required for the development of spasticity after spinal cord injury and during amyotrophic lateral sclerosis (ALS). We sought here to provide direct evidence for a role of brainstem serotonin neurons in spasticity. Methods: SOD1 (G37R) mice expressing a conditional allele of an ALS‐linked SOD1 mutation were crossed with Tph2‐Cre mice expressing Cre in serotonergic neurons. Measurement of long‐lasting reflex using electromyography, behavioral follow‐up, and histological techniques was used to characterize spasticity and motor phenotype. Results: Deleting mutant SOD1 expression selectively in brainstem serotonin neurons was sufficient to rescue loss of TPH2 immunoreactivity and largely preserve serotonin innervation of motor neurons in the spinal cord. Furthermore, this abrogated constitutive activity of 5‐HT2B/C receptors and abolished spasticity in end‐stage mice. Consistent with spasticity mitigating motor symptoms, selective deletion worsened motor function and accelerated the onset of paralysis. Interpretation: Degeneration of serotonin neurons is necessary to trigger spasticity through the 5‐HT2B/C receptor. The wide range of drugs targeting the serotonergic system could be useful to treat spasticity in neurological diseases. Ann Neurol 2017;82:444–456